2021
DOI: 10.3389/fphys.2021.735986
|View full text |Cite
|
Sign up to set email alerts
|

Human Physiological Responses to a Single Deep Helium-Oxygen Diving

Abstract: Objective: The objective of this study was to explore whether a single deep helium-oxygen (heliox) dive affects physiological function.Methods: A total of 40 male divers performed an open-water heliox dive to 80 m of seawater (msw). The total diving time was 280 min, and the breathing helium-oxygen time was 20 min. Before and after the dive, blood and saliva samples were collected, and blood cell counts, cardiac damage, oxidative stress, vascular endothelial activation, and hormonal biomarkers were assayed.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The research showed that there were statistically significant differences between the results obtained after exposure to conditions of a 60 m dive and the values measured for the non-divers group (p = 0.0494). VCAM-1 is expressed exclusively on the activated endothelium following vascular insult, and therefore, is a marker of a proinflammatory endothelium, as a study by Bao et al [13] showed.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The research showed that there were statistically significant differences between the results obtained after exposure to conditions of a 60 m dive and the values measured for the non-divers group (p = 0.0494). VCAM-1 is expressed exclusively on the activated endothelium following vascular insult, and therefore, is a marker of a proinflammatory endothelium, as a study by Bao et al [13] showed.…”
Section: Discussionmentioning
confidence: 97%
“…The changes in VCAM-1, as a result of diving to a depth of 60 m, were highly statistically significant. A study by Bao et al [13] found that diving caused significantly reduced VCAM-1 levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation